PENGARUH METODE DISKUSI TERHADAP HASIL BELAJAR IPA DENGAN TEMA ORGAN GERAK HEWAN DAN MANUSIA DI KELAS V MIS IKHLAASHUL’AMAL SEBAWI TAHUN PELAJARAN 2021/2022 - Mega Mega; Purniadi Putra; Rona Rona (CV. Adiba Aisha Amira, 2025)
This research aims to explain: 1) Science learning outcomes before using the Discussion Method with the theme of animal and human movement organs in class V MIS Ikhlaashul'Amal Sebawi. 2) Science learning results after using the Discussion Method with the theme of animal and human movement organs in class V Ikhlaashul'Amal Sebawi. 3) the significant influence of the Discussion Method on science learning outcomes with the theme of animal and human movement organs in class V MIS Ikhlaashul'Amal Sebawi. The type of research used is quantitative. The population in this study were fifth grade students and the sample in this study was 30 people. Data collection tools used the Independent Simple T-test and Nonparametric t-test: Mann Whitney. The results of this research can be concluded as follows: 1) The learning outcomes of Class V MIS Ikhlaashul'Amal Sebawi students before and after using the discussion method in the experimental group were classified as